2014
DOI: 10.1021/jp5089564
|View full text |Cite
|
Sign up to set email alerts
|

Three Rate-Constant Kinetic Model for Permanganate Reactions Autocatalyzed by Colloidal Manganese Dioxide: The Oxidation ofl-Phenylalanine

Abstract: The reduction of permanganate ion to MnO(2)-Mn(2)O(3) soluble colloidal mixed oxide by l-phenylalanine in aqueous phosphate-buffered neutral solutions has been followed by a spectrophotometric method, monitoring the decay of permanganate ion at 525 nm and the formation of the colloidal oxide at 420 nm. The reaction is autocatalyzed by the manganese product, and three rate constants have been required to fit the experimental absorbance-time kinetic data. The reaction shows base catalysis, and the values of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…This variation of the rate constants can be ascribed to the decrease of the pH as the reaction advanced caused by the release of protons from the amino acid to coordinate with Cr(III), suggesting the involvement of base catalysis that was confirmed later by independent experiments. Actually, the occurrence of systematic experimental errors leading to rate coefficients showing a dependence on the value of the limiting reactant initial concentration is somehow ubiquitous in kinetic studies, especially when two or three rate constants are required to account for the observed absorbance versus time curves. Therefore, the rate constants obtained in this work must be considered as average values for the pH range covered in each kinetic experiment.…”
Section: Resultsmentioning
confidence: 99%
“…This variation of the rate constants can be ascribed to the decrease of the pH as the reaction advanced caused by the release of protons from the amino acid to coordinate with Cr(III), suggesting the involvement of base catalysis that was confirmed later by independent experiments. Actually, the occurrence of systematic experimental errors leading to rate coefficients showing a dependence on the value of the limiting reactant initial concentration is somehow ubiquitous in kinetic studies, especially when two or three rate constants are required to account for the observed absorbance versus time curves. Therefore, the rate constants obtained in this work must be considered as average values for the pH range covered in each kinetic experiment.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Permanganate oxidations have been reviewed extensively. [21][22][23][24][25][26][27][28][29] Definitive works of Simandi, [30][31][32][33][34] Wiberg, [35][36][37] Freeman, [38][39][40] Perez-Benito, [41][42][43][44][45] Lee, [46][47][48][49] and Stewart [50][51][52] have greatly contributed to our understanding of the mechanisms of oxidations of a diverse group of organic compounds. These include aromatic hydrocarbons (C-H oxidation), 35,53,54 alcohols, 50,51 aldehydes, 37 alkenes, 30,38,39 oxalic acid, [55][56][57][58][59] amines, 52,…”
Section: Introductionmentioning
confidence: 99%
“…These include aromatic hydrocarbons (C-H oxidation), 35,53,54 alcohols, 50,51 aldehydes, 37 alkenes, 30,38,39 oxalic acid, [55][56][57][58][59] amines, 52,60 sulfoxides, 61 and amino acids. [41][42][43][44][45] Permanganate oxidations are inherently complex due to a number of intermediates resulting from initial two and one electron reductions of Mn(VII). Both Mn(V) and Mn(VI) have no known aqueous chemistry except in a highly alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations